Memorias de silencios : Espacio y función de las mujeres en el archivo - Carreño Corchete, Esther (Tábula, 2018)
Se dibuja una panorámica general sobre los archivos en femenino en nuestro país. Por una parte, se realiza un breve recorrido por el movimiento de lucha para la igualdad de las mujeres y por los archivos feministas. La documentación generada por mujeres militantes de este movimiento y la creación de estos archivos a partir de los años 70, han sido procesos casi desconocidos con una visibilidad muy limitada. Este patrimonio se encuentra solapado entre el fondo documental de bibliotecas y centros de documentación de mujeres, pero muy disperso. Se hace necesaria la tarea de unificación en un archivo propio y la creación de redes nacionales e internacionales. This paper presents a historical and general overview about women archivist and archives specialized in women and gender. On the one hand, a general review of the feminist archives in Spain is given. The documentation generated by militant women of this movement and the creation of these archives have been almost unknown processes with a very limited visibility. That feminist documentary heritage overlaps with documents stored in libraries and women’s documentation centers, but it is very dispersed. The unification in an only archive and the creation of national and international networks becomes a necessary task. In parallel, the profession of archivist in Spain is analyzed from a historical and gender perspective, beginning with the period of the creation of the Facultative Body of Archivists-Librarians in 1858 to the present.